Age-specific distribution of serum anti-mullerian hormone and antral follicle count in Indian infertile women - Devika Gunasheela; Rajaam Murali; Lohith Chengappa Appaneravanda; Brigitte Gerstl; Arun Kumar; Nishanthini Sengeetha; Hita Nayak; P M Chandrikadevi (Wolters Kluwer Medknow Publications, 2021)
Background: Ovarian reserve declines with age. However, there are considerable ethnic differences in the decline of ovarian reserve between individuals. Aim: This study aimed to make age-specific percentile charts of anti-Mullerian hormone (AMH) and antral follicle count (AFC) in Indian infertile women and to find the proportion of young women with low ovarian reserve. Setting and Design: This was a retrospective data analysis of AMH and AFC of 5525 infertile women from August 2015 to December 2018. Materials and Methods: Infertile women aged 20-44 years, with body mass index 18-32 kg/m2 and having both ovaries were included in the study. Women with pituitary/adrenal disorders, malignancy, total AFC >40, tuberculosis, endometriosis, autoimmune disorders, smoking, chemotherapy, radiotherapy and recent ovarian surgery were excluded from the study. Statistical Analysis: Comparison between groups was done by Chi-square test. Results: About 14.5% of women <35 years and 50.5% of women >35 years had low AMH values (<1.1 ng/ml). In addition, 5.6% of women <35 years and 23.6% of women >35 years had a low AFC of ≤5. In this study, 55.7% of women who had low AMH and 50.7% who had low AFC were <35 years of age. The median AMH values were 4.23 ng/mL in 20-25 years' age group, 3.48 ng/mL in women aged 26-30 years, 2.43 ng/mL in women aged 31-35 years, 1.28 ng/mL in women aged 36-40 years and0.52 ng/mL in 40-44 years' age group. The median AFCs were 20, 18, 14, 10 and 6 for each of the age groups, respectively. Conclusion: This study suggests that approximately more than half of the infertile women who were tested to have low ovarian reserve were <35 years of age.